ANALISIS WACANA KRITIS NORMAN FAIRCLOUGH TERHADAP PEMBERITAAN MEDIA ONLINE PADA BERITA GEJOLAK PENGUNGSI ROHINGYA - Agus Dadang Hermawan; Agus Hamdani (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
Critical Discourse Analysis (CDA) examines language as 'discourse,' where language is understood as one element within social processes that dialectically relate to each other. Critical discourse analysis precisely aims to explore these dialectical interconnections within the tradition of critical social science. In this research, the researcher will employ Norman Fairclough's model of critical discourse analysis, which examines discourse analysis through three theories: Text Analysis (Microstructural) related to cohesion and coherence, grammar, and diction; Production Practice Analysis (Mesostructural) dealing with the text production process, text dissemination, and text consumption, such as work patterns, workflow, and routines in news production; Social Cultural Practice Analysis (Macrostructural) related to situational, institutional, and social aspects. This study utilizes a qualitative descriptive method to deepen the critical analysis description of news discourse. The research data consists of words, phrases, or sentences in two online news discourses supporting the research problem. The data collection technique employed is documentary study. The news regarding the arrival of Rohingya refugees in Aceh published by VIVA.co.id becomes the focus of critical discourse analysis using Norman Fairclough's approach. This news reflects the text production process involving microstructural, mesostructural, and macrostructural aspects. In microstructural analysis, language use and representation are highlighted. Phrases like "coming to Indonesia using old boats" and quotes from netizens create negative stereotypes about Rohingya refugees. Social interactions are reflected in conflicts and societal concerns represented by these comments. In mesostructural analysis, the selection of topics, framing, and source determination becomes the focus. Choosing to report the Rohingya refugee issue with a predominantly negative framing reflects editorial production decisions influenced by preferences. Determining sources from netizens and UNHCR creates variations in perspectives. Macrostructural analysis highlights the social, political, and cultural values that shape the news. The Rohingya refugee crisis and global migration politics form the macro background influencing news production. Indonesian cultural values and ideology are reflected in the stigmatization of refugees. In conclusion, this critical discourse analysis reveals how text production practices, social interactions, and macrostructural contexts are interconnected. This news not only reflects internal language and media dynamics but is also tied to power, ideology, and cultural values within society. This analysis opens up space for a deeper understanding of narrative construction and its impact on public perceptions of Rohingya refugees in Indonesia. Keywords: Critical Discourse Analysis, Norman Fairclough, News.